URGENT PLEASE Solve the equation using the quadratic formula. 3x^2 – 18 = -6

Question

URGENT PLEASE Solve the equation using the quadratic formula. 3x^2 – 18 = -6

in progress 0
Cora 2 months 2021-10-14T17:50:23+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-14T17:51:51+00:00

    Answer:

    x = 2 and x = -2

    Step-by-step explanation:

    The quadratic formula of a quadratic of the form ax² + bx + c is:

    x = \frac{-b+\sqrt{b^2-4ac} }{2a} or x = \frac{-b-\sqrt{b^2-4ac} }{2a}

    Here, our equation is: 3x² – 18 = -6. Let’s move all the terms to one side:

    3x² – 12 = 0

    a = 3 and c = -12. Notice that since there’s no x term, b = 0.

    Plug these into the quadratic formula:

    x = \frac{0+\sqrt{0^2-4*3*(-12)} }{2*3}=\frac{\sqrt{144} }{6}=12/6=2  

    or

    x = \frac{0-\sqrt{0^2-4*3*(-12)} }{2*3}=\frac{-\sqrt{144} }{6}=-12/6=-2

    So, x = 2 and x = -2.

    0
    2021-10-14T17:52:00+00:00

    Answer: x = -2, x = 2

    Step-by-step explanation:

    The quadratic formula:

    x=\frac{-b+\sqrt{b^2-4ac} }{2a} \\\\AND\\\\x = \frac{-b-\sqrt{b^2-4ac} }{2a} \\

    You can find the variables a, b, and c in the standard form of a quadratic equation:

    f(x)=ax^2 + bx+c

    Your equation:

    f(x)=3x^2 + 0x -12

    The variables are:

    a = 3

    b = 0

    c = -12

    Substitute those for the variables in the quadratic formula:

    x=\frac{-0+\sqrt{0-(4*3*-12)}}{2(3)} \\\\AND\\\\x=\frac{-0-\sqrt{0-(4*3*-12)}}{2(3)} \\

    You can simplify this to get:

    x=\frac{-\sqrt{144}}{6} \\

    (or positive square root of 144.)

    The square root of 144 is 12, and 12/6 = 2.

    The x-values are -2 and 2.

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )